Stres i wypalenie zawodowe w pracy ratowników medycznych = Stress and a burn-out syndrome at work among paramedics - Żurowska-Wolak, Magdalena; Wolak, Bartłomiej; Mikos, Marcin; Juszczyk, Grzegorz; Czerw, Aleksandra (Journal of Education, Health and Sport, 2015)
Żurowska-Wolak Magdalena, Wolak Bartłomiej, Mikos Marcin, Juszczyk Grzegorz, Czerw Aleksandra. Stres i wypalenie zawodowe w pracy ratowników medycznych = Stress and a burn-out syndrome at work among paramedics. Journal of Education, Health and Sport. 2015;5(7):43-50. ISSN 2391-8306. DOI 10.5281/zenodo.19112 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A43-50 https://pbn.nauka.gov.pl/works/575047 http://dx.doi.org/10.5281/zenodo.19112 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015. Stres i wypalenie zawodowe w pracy ratowników medycznych Stress and a burn-out syndrome at work among paramedics Magdalena Żurowska-Wolak (1), Bartłomiej Wolak (2), Marcin Mikos (3), Grzegorz Juszczyk (4), Aleksandra Czerw (4) 1. Wydział Nauk o Zdrowiu, Uniwersytet Jagielloński – Collegium Medicum, Kraków 2. Krakowskie Pogotowie Ratunkowe; Kraków 3. Instytut Zdrowia Publicznego, Uniwersytet Jagielloński – Collegium Medicum, Kraków 4. Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny, Warszawa Adres do korespondencji: Magdalena Żurowska-Wolak tel: 503 196 836; e- mail: m_zurowska@vp.pl Streszczenie: Zawód ratownika medycznego jest jednym zawodów, w których narażenie na stres jest wysokie oraz istnieje ryzyko wystąpienia zespołu wypalenia zawodowego. Celem badania było poznanie sposobów radzenia sobie ze stresem, stosowanych przez ratowników medycznych oraz występowania wśród nich objawów wypalenia zawodowego. Najczęstszym z nich było występowanie dużego zmęczenia po pracy. Większość badanych (64%) potwierdziła wykorzystywanie konstruktywnych sposobów radzenia sobie ze stresem, jak również niekonstruktywne stosowanie używek, w szczególności kofeiny i nikotyny, których spożycie wzrastało w sytuacjach trudnych. Na podstawie badań można wnioskować, że wśród ratowników medycznych, pracujących w Krakowie i okolicach, występuje niebezpiecznie dużo objawów wypalenia zawodowego. Świadczy to o potrzebie stworzenia i realizacji przez ich pracodawców działań, obniżających poziom stresu wśród pracowników oraz zapobiegających wystąpieniu wypalenia zawodowego – jak debriefing, trenieng technik radzenia sobie ze stresem czy wspierania aktywności fizycznej. Jest to o tyle istotne, iż skutki stresu oraz wypalenia odczuwają nie tylko sami ratownicy. Skutki te są dolegliwe także dla pracodawców, którzy zatrudniają gorzej funkcjonujących pracowników oraz pacjentów, otrzymujących usługi o niższej jakości. Abstract: Paramedics are one of the professions where the risk of exposure to stress is high as well as the risk of occurrence of the burnout syndrome. The aim of the study was to analyze methods of stress reduction and symptoms of the burnout syndrome among 122 paramedics from Kraków and surrounding area. The most prevalent symptom was severe tiredness after working hours. The majority of respondents (64%) confirmed using constructive methods of stress reduction, however potentially dangerous use of alcohol, cigarettes was also observed especially in difficult situations. The results showed that in the research group the occurrence of alarming symptoms of the burnout syndrome was numerous. Therefore there is a need to define and implement appropriate activities aiming at stress reduction training – like debriefing, training on resilience or support of physical activity. It is highly important since the outcomes of burnout will affect not only paramedics themselves, but also their employers and patients. Słowa kluczowe: ratownik medyczny, stres, wypalenie zawodowe. Key words: paramedic, stress, burnout syndrome.